2021
DOI: 10.1108/ccsm-05-2021-0093
|View full text |Cite
|
Sign up to set email alerts
|

Host country national support to expatriates: a motivated information processing perspective

Abstract: PurposeThe support of host country nationals (HCNs) is a key determinant of expatriate adjustment and performance. The purpose of this paper is to explore underlying motivations for their support to expatriates. Previous research has shown that HCNs with pro-social motivation are more likely to help expatriates. Drawing upon motivated information processing in groups (MIP-G) theory, the authors test whether epistemic motivation moderates the observed relationship between pro-social motivation and HCNs’ support… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 88 publications
(174 reference statements)
0
4
0
Order By: Relevance
“…There are more than 100,000 voluntary associations in Denmark [15], and approximately 90% of Danes are members of such social groups [16]. Russell (2015) discusses how these associations fit with Danish values of equality, harmony and unity and that those participating in these communities, whether locals or foreigners, build pro-social motivational factors of trust and amiability, which can lead to supportive HCN–expatriate information exchange (Mahajan and De Silva, 2012; Sonesh and DeNisi, 2016; Varma et al ., 2016; Yoon et al ., 2022).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are more than 100,000 voluntary associations in Denmark [15], and approximately 90% of Danes are members of such social groups [16]. Russell (2015) discusses how these associations fit with Danish values of equality, harmony and unity and that those participating in these communities, whether locals or foreigners, build pro-social motivational factors of trust and amiability, which can lead to supportive HCN–expatriate information exchange (Mahajan and De Silva, 2012; Sonesh and DeNisi, 2016; Varma et al ., 2016; Yoon et al ., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Considerable research has demonstrated that “breaking out of the expatriate bubble” and building local host country national (HCN) social connections, both in and outside the workplace, can be very helpful through information exchange in facilitating effective adjustment (Sonesh and DeNisi, 2016; Van Bakel et al. , 2017; Varma et al ., 2016; Yoon et al ., 2022). Selmer et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As has been done in prior research, team epistemic motivation was assessed by proxy using a team reflexivity measure (e.g., De Dreu, 2007; Otte et al, 2017; Yoon et al, 2021). Team reflexivity refers to “a deliberate process of discussing team goals, processes, or outcomes” (Schippers et al, 2014; p. 733).…”
Section: Methodsmentioning
confidence: 99%